Assessing the Landscape and Proposing a Way Forward: The Teaching of Scandinavian Politics in Canadian Universities - Ugland, Trygve (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2024)
This paper offers a first status report and an analysis of the teaching of Scandinavian politics in Canadian universities. Based on a questionnaire sent out to the 57 affiliated member departments of the Canadian Political Science Association (CPSA) in 2022, the paper identifies a clear mismatch between the attention paid to various aspects of the Scandinavian political model among academics and society more generally in Canada, and the very limited number of courses specifically dedicated to Scandinavian politics at Canadian universities during the 2018-2022 period. The paper makes some recommendations on how to promote and integrate Scandinavian politics content more actively into university teaching. Moreover, the paper presents a dedicated course on Scandinavian politics at a Canadian university as an example. The importance of a comparative and interdisciplinary approach to Scandinavian politics is here highlighted.